Redesign and Testing of Coconut Fiber Chopping Machine Using 3 Phase 7.5 HP Electric Motor Drive - Kawulur, Meidy Pingkan Yosefin; Pinangkaan, Niko (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The use of machines that shred coconut fiber and are powered by diesel engines in the market has not yet enhanced consumer comfort and efficiency. This is because its combustion results in CO? and NOx, causing air and noise pollution. It is relatively large and requires regular maintenance, which demands space and incurs significant costs. Therefore, an efficient and optimal machine for shredding coconut fiber is needed, one that reduces noise to avoid being loud and is pollution-free. The coconut fiber shredder, powered by an electric motor, is an innovation that offers a solution for producing household products and agricultural fertilizers aimed at enhancing comfort and efficiency for consumers, thereby increasing economic value in the community. This study aims to develop an environmentally friendly machine for shredding coconut fiber, powered by a 3-phase 7.5 hp electric motor for low noise, minimal vibration, and improved time efficiency. The resulting machine facilitates the production of coconut coir and powder, which can be utilized for household and agricultural products. Contribution to Sustainable Development Goals:SDG 7 : Affordable and Clean EnergySDG 9 : Industry, Innovation and InfrastructureSDG 12 Responsible Consumption and Production): SDG 13: Climate Action SDG 8: Decent Work and Economic Growth